2011
DOI: 10.1542/peds.2010-0938
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Attitudes Toward Pediatric Genetic Testing for Common Disease Risk

Abstract: As genetic susceptibility testing for common, adult-onset health conditions proliferates, pediatricians should anticipate parents' interest in testing children and be prepared to facilitate informed decision making about such testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 34 publications
(16 reference statements)
8
85
0
Order By: Relevance
“…The bottom line in the lay public group was when it comes to information with respect to themselves (Daack-Hirsch 2012) or their children; they wanted the option to know about it. A similar finding has been reported in other publications engaging the lay public (Tercyak et al 2011;Townsend et al 2012). Lay public participants also felt that parents were the best recipients and keepers of information pertaining to their children.…”
Section: Discussionsupporting
confidence: 86%
“…The bottom line in the lay public group was when it comes to information with respect to themselves (Daack-Hirsch 2012) or their children; they wanted the option to know about it. A similar finding has been reported in other publications engaging the lay public (Tercyak et al 2011;Townsend et al 2012). Lay public participants also felt that parents were the best recipients and keepers of information pertaining to their children.…”
Section: Discussionsupporting
confidence: 86%
“…It is particularly discouraged to use home-kit genetic testing (available for certain diseases) to assess a "risk to develop" a disease (see section below) and notably on children. In addition to the risks of inaccurate results, inaccurate interpretations, potentially harmful interventions and alteration in family dynamics will most likely results from this with negative consequences [12,13]. Furthermore, in the context of PM tests, it is important to get across the message that a test is only valid for a certain time in the course of a disease and only reflect a patient's history up to that point in time (notably taking in consideration previously failed treatment options).…”
Section: Relatives Of Patientsmentioning
confidence: 99%
“…11 The potential psychological impacts, along with concerns regarding family planning, fertility, lifestyle choices and health management, 5,12 indicate individualized management and genetic counseling should remain a priority. 3,10 A large body of research has investigated public [13][14][15][16][17] and patient 1,3,[18][19][20][21][22] perceptions of genetic testing, and reported that despite low levels of understanding, perceived benefits outweigh the risks. Patients' most highly-rated benefits include increased knowledge, better outcomes, and more effective prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' most highly-rated benefits include increased knowledge, better outcomes, and more effective prevention strategies. 3,13,15,18,20,22 …”
Section: Introductionmentioning
confidence: 99%